Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis Classpoint terhadap Motivasi Belajar Siswa pada Pembelajaran Pendidikan Agama Kristen di Kelas Xi SMA Negeri 1 Sibolangit - Nurlina; Bangun Munthe; Bangun (CV. Creative Tugu Pena, 2024)
The aim of this research is to determine the effect of using Classpoint-based interactive learning media on student learning motivation in Christian religious education learning in class XI of SMA Negeri 1 Sibolangit. This research uses descriptive quantitative methods, and the sampling technique used is simple random sampling with a sample size of 34 people. The data collection tool is a questionnaire in the form of multiple choices which has been carried out with instrument validation tests. After carrying out the Pearson product moment correlation statistical test. From the results of the correlation test, it was obtained (r) 0.63 with a determination test of 39.69% and to find out whether the correlation coefficient was significant or not at the level (a) = 0.05, a